Anaerobic Treatability of Pharmaceutical Wastewaters - Pallavi, V.; Daga, Kailash; Gehlot, Poonam; Chaudhary, Santosh (Asian Journal of Chemistry, 2010)
This paper mainly focus on the anaerobic treatability of pharmaceutical wastewater. Wastes with high BOD:COD ratio are studied in a batch anaerobic digester, with acclimatized seed sludge. In the present study, an attempt has been made to evaluate the efficiency of batch type anaerobic reactor for pharmaceutical waste waters. Continous monitoring of parameters like BOD, COD, pH, Volatile fatty acids, alkalinity, sulphates were carried out to evaluate the performance of the reactor. The studies revealed that a maximum COD reduction of 73 % is obtained.